Corticosteroids for Guillain‐Barré syndrome - Hughes, Richard AC (Cochrane Database Syst Rev, 2016)
BACKGROUND: Guillain‐Barré syndrome (GBS) is an acute paralysing disease caused by inflammation of the peripheral nerves, which corticosteroids would be expected to benefit. OBJECTIVES: To examine the ability of corticosteroids to hasten recovery and reduce the long‐term morbidity from GBS. SEARCH METHODS: On 12 January 2016, we searched the Cochrane Neuromuscular Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, and Embase. We also searched trials registries. SELECTION CRITERIA: We included randomised controlled trials (RCTs) or quasi‐RCTs of any form of corticosteroid or adrenocorticotrophic hormone versus placebo or supportive care alone in GBS. Our primary outcome was change in disability grade on a seven‐point scale after four weeks. Secondary outcomes included time from randomisation until recovery of unaided walking, time from randomisation until discontinuation of ventilation (for those ventilated), death, death or disability (inability to walk without aid) after 12 months, relapse, and adverse events. DATA COLLECTION AND ANALYSIS: The review authors used standard methods expected by Cochrane. MAIN RESULTS: The review authors discovered no new trials in the new searches in June 2009, November 2011, or January 2016. Six trials with 587 participants provided data for the primary outcome. According to moderate quality evidence, the disability grade change after four weeks in the corticosteroid groups was not significantly different from that in the control groups, mean difference (MD) 0.36 less improvement (95% confidence intervals (CI) 0.16 more to 0.88 less improvement). In four trials of oral corticosteroids with 120 participants in total, there was very low quality evidence of less improvement after four weeks with corticosteroids than without corticosteroids, MD 0.82 disability grades less improvement (95% CI 0.17 to 1.47 grades less). In two trials with a combined total of 467 participants, there was moderate quality evidence of no significant difference of a disability grade more improvement after four weeks with intravenous corticosteroids (MD 0.17, 95% CI ‐0.06 to 0.39). According to moderate quality evidence, there was also no significant difference between the corticosteroid treated and control groups for improvement by one or more grades after four weeks (risk ratio (RR) 1.08, 95% CI 0.93 to 1.24) or for death or disability after one year (RR 1.51, 95% CI 0.91 to 2.5). We found high quality evidence that the occurrence of diabetes was more common (RR 2.21, 95% CI 1.19 to 4.12) and hypertension less common (RR 0.15, 95% CI 0.05 to 0.41) in the corticosteroid‐treated participants. AUTHORS' CONCLUSIONS: According to moderate quality evidence, corticosteroids given alone do not significantly hasten recovery from GBS or affect the long‐term outcome. According to very low quality evidence, oral corticosteroids delay recovery. Diabetes requiring insulin was more common and hypertension less common with corticosteroids based on high quality evidence.